Applied positive psychology : integrated positive practice - Lomas, Tim, 1979-; Hefferon, Kate; Ivtzan, Itai (Los Angeles : SAGE, 2014)
If you think you know what positive psychology is, think again! This book offers a new integrative vision for making life better that takes in the body and the brain, culture and society, childhood and development __ A must read for students.
chapter 1. Preparing for the journey -- chapter 2. The mind -- chapter 3. The body and the brain -- chapter 4. Culture and society -- chapter 5. Childhood and development -- chapter 6. Occupations and organisations -- chapter 7. Religion and spirituality -- chapter 8. Ethical and reflective practice.
Includes bibliographical references (pages 174-215) and index.
Description based on MARC record for print version.
Keywords: Positive psychology; Positive psychology; Psychology, Applied